The feral detective : a novel - Lethem, Jonathan (Ecco, an imprint of HarperCollinsPublishers, 2018)
Phoebe Siegler first meets Charles Heist in a shabby trailer on the eastern edge of Los Angeles. She<U+2019>s looking for her friend<U+2019>s missing daughter, Arabella, and hires Heist to help. A laconic loner who keeps his pet opossum in a desk drawer, Heist intrigues the sarcastic and garrulous Phoebe. Reluctantly, he agrees to help. The unlikely pair navigate the enclaves of desert-dwelling vagabonds and find that Arabella is in serious trouble<U+2014>caught in the middle of a violent standoff that only Heist, mysteriously, can end. Phoebe<U+2019>s trip to the desert was always going to be strange, but it was never supposed to be dangerous. . .